SEDIMENTARY AGE OF STRATA IN THE SALAWUSU RIVER BASIN AND CLIMATIC CHANGING - Jin H.; Li M.; Dong G.; Zhao H.; Sun Z.; Su Z. (My University, 2007)
The Salawusu river basin is situated in the transition zone between desert and loess, and also in a fragile ecotone of northern China. This region is an ideal site for research on the global change due to its high sensitivity to global climate variation. We conducted geological dating for strata in the study region and analyzed the stratigraphic climatic proxies, based on which and according to the climate-stratum comparison method we further divided the strata in the Salawusu river basin into the following sequences: (1) lacustrine and aeolian facies of Holocene dated at 0-11.5 ka BP, with warm-humid climate in the early and middle phase and arid climate in the late phase; (2) Late Pleistocene aeolian facies of the Chengchuan Group dated at 11.5-80 ka BP, with arid-cold climate; (3) Late Pleistocene lacustrine facies of the Salawusu Group dated at 80-140 ka BP, with warm-humid climate; (4) interbed of fluvial and aeolian facies of Middle Pleistocene dated at 140-190 ka BP, with climate fluctuating between arid-cold and semiarid-warm cool; (5) alluvial facies of Middle Pleistocene dated at 190-220 ka BP, with warm-humid climate. In a word, the climate either in warm-humid phase or in arid-cold phase has been fluctuating frequently since the late Middle Pleistocene, indicating remarkable instability of climatic change.
Keywords: CLIMATIC CHANGE; GLOBAL CHANGE; SALAWUSU RIVER BASIN; STRATIGRAPHIC AGE; STRATIGRAPHIC DIVISION; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен